Effect of different arsenic and biochar levels on soil microbial population and enzymatic activity - Pandey, Astha; Singh, Satish Kumar; Sharma, Sheetal; Mishra, Ajay Kumar; Jatav, Surendra Singh; Patra, Abhik; Bahuguna, Ayush; Mukharjee, Sayon; Yadav, Bharti; Pankaj, Bhanupriya (Sciencedomain International, 2023)
Arsenic (As) poses a pervasive environmental contamination problem on a global scale. Human activities have significantly contributed to the extensive presence of arsenic (As) in soils. Recently, there has been growing interest in exploring the potential of biochar in addressing the issue of As-contaminated soils. This study focused on evaluating the effects of two types of biochar, namely straw biochar and iron-modified biochar, on the composition of soil microbial communities and enzymatic activity in soil contaminated with arsenic. After conducting a pot experiment for a duration of 9 months, the microbial communities and enzymatic activity were analyzed. Biochar refers to carbon-rich porous solids that are produced by heating biomasses under low oxygen conditions. These biochars are regarded as environmentally friendly sorbents that can be employed for the treatment of different types of arsenic contamination. The increased abundance of soil microbial populations and the enhanced enzymatic properties suggest that biochar fosters the richness and diversity of bacterial communities. Consequently, these improvements in the soil environment and biological quality highlight the potential of iron-modified biochar as an alternative agent for remediating arsenic-contaminated soils.